Knowledge and Attitudes of Pregnant Women during Antenatal Care Visit at Abi Ummi DW Sarmadi Clinic Palembang Relationship Knowledge and Attitude of Pregnant Women Against Antenatal Care Visit In Abi Ummi DW Sarmadi Clinic Palembang - Erike Septa Prautami (Science Midwifery, 2018)
Background Antenatal care is an important way to monitor and support and detect the health of pregnant women with normal mother normal pregnancy. The objective of this study is to know the relationship of knowledge and attitudes of pregnant women against antenatal care visit in Abi Ummi DW Sarmadi Clinic Palembang. The Methods used in this research are analytic surveys with the approach of "cross sectional" and samples are taken with consecutive sampling technique with 64 respondents. This data collect use questionnaire and bivariate analysis with chi-square tests. The result there is a significant relationship between knowledge with antenatal care visited in Abi Ummi DW Sarmadi Clinic Palembang with p value = 0,000, then significant relationship between attitude with antenatal care visited in Abi Ummi DW Sarmadi Clinic Palembang with p value = 0,000.